Service users’ perception and attitude toward telemedicine-based treatment for substance use disorders: A qualitative study from India - Abhishek Ghosh; Tathagata Mahintamani; P. V. Aswathy; Debasish Basu; Surendra K. Mattoo; B. N. Subodh; Renjith R. Pillai; Manpreet Kaur (Indian Journal of Psychiatry)
Aim: We aimed to assess the service user’s acceptability, feasibility, and attitude toward telemedicine practice and compare it with in-person consultation in substance use disorder (SUD). Materials and Methods: We recruited 15 adult patients with SUD who accessed both telemedicine and in-person care. We conducted in-depth interviews on awareness and access, facilitators and barriers, treatment satisfaction, and therapeutic relationship in the telemedicine context. We performed a conventional content analysis of the interview excerpts and used inductive and deductive coding. We assumed that social, personal, and logistic contexts influence patients’ perceptions and experiences with telemedicine-based addiction care (TAC). Results: Most participants were middle-aged men (40.5 years, 86.7%), dependent on two or more substances (86.7%), and had a history of chronic, heavy substance use (use ~16 years, dependence ~11.5 years). Patients’ perspectives on TAC could broadly be divided into three phases: pre-consultation, consultation, and post-consultation. Patients felt that TAC improved treatment access with adequate autonomy and control; however, there were technical challenges. Patients expressed privacy concerns and feared experiencing stigma during teleconsultation. They reported missing the elaborate inquiry, physical examination, and ritual of visiting their doctors in person. Additionally, personal comfort and technical difficulties determine the satisfaction level with TAC. Overall perception and suitability of TAC and the decision to continue it developed in the post-consultation phase. Conclusion: Our study provides an in-depth insight into the barriers and facilitators of telemedicine-based SUD treatment access, use, and retention; it also helps to understand better the choices and preferences for telehealth care vis-à-vis standard in-person care for SUDs.